Modulatory Effects of CD14+CD16++ Monocytes on CD14++CD16− Monocytes : A Possible Explanation of Monocyte Alterations in Systemic Lupus Erythematosus (2014)
ABSTRACT: Objective In various chronic inflammatory processes, both the proportion and numbers of monocyte subsets are altered. In systemic lupus erythematosus (SLE), this has not been clearly determined. The monocyte subpopulations in patients with SLE, patients with other autoimmune diseases, and healthy controls were evaluated. The effects of nonclassic monocytes and apoptotic cells (ACs) on the differentiation and function of CD14++CD16− monocytes were also studied. Methods Monocyte subpopulations derived from the blood samples of SLE patients (n = 88), patients with other autoimmune diseases (n = 37), and healthy control subjects (n = 61) were separated by fluorescence-activated cell sorting. To evaluate the effect of CD14+CD16++ monocytes and ACs on the differentiation of CD14++CD16− monocytes, we developed a coculture model of highly purified sorted monocyte subpopulations, which were reconstituted with defined proportions of CD14++CD16− and CD14+CD16++ monocytes in the presence or absence of ACs. After differentiation into macrophages, CD3+ lymphocytes were added, and the proliferating cells and CD3+IFNγ+ cells were evaluated. A cytokine bead array panel was used to test the coculture supernatants. Results There was a reduction in CD14+CD16++ monocytes in patients with active SLE. Monocytes from SLE patients had decreased expression of HLA–DR and decreased ability to bind and phagocytize ACs. In healthy controls, but not SLE patients, treatment with macrophages derived from CD14+CD16++ monocytes reduced T cell proliferation and proliferating CD3+IFNγ+ cells and increased the accumulation of tumor necrosis factor α, interleukin-10 (IL-10), and IL-1β. Conclusion Our findings show that CD14+CD16++ monocytes, a population that is reduced and nonfunctional in SLE patients, have modulatory effects on CD14++CD16− monocytes and T cells.